Trade liberalization and food security in Nepal - Pyakuryal, Bishwambher; Thapa, Ganesh B.; Roy, Devesh (International Food Policy Research Institute, 2005)
Among South Asian countries, Nepal has liberalized most extensively during the 1980s and 1990s on both fronts, domestic and external. Nepal is a least developed country with a gross national product of US $235 per capita in 2001 and second lowest per capita wealth in the world. In South Asia, Nepal has the lowest per capita income, highest dependence of population on agriculture and second highest poverty rate. At the same time, on an average, Nepal has the lowest tariffs in South Asia and has taken several steps to downsize its public distribution system and remove a host of agricultural subsidies. This twin scenario where the lowest per capita income country is perhaps also the most liberalized makes for an interesting case for policy analysis. This paper reviews the outcomes from the liberalization policies followed by Nepal relating to food security.